Legacy of Prof. Juraj Korpáš: International Impact of Slovak School of Experimental Respirology - Plevkova, J; Poliacek, I (Physiological research, 2020)
Human health is the main role of medical research. Scientists were always intrigued by disease prevention, their diagnostics and proper treatment. In fact, research in medicine is always directed towards the improvement of the health care and improvement of the quality of life of the target population. Nowadays, physiological research, which is the base stone for clinical research, progresses fast forward, providing new information about body functions in health and diseases. This obvious progress is associated with modern methods, such as neuronal tracing, patch-clamp methods, electrophysiology, molecular biology and many more, which supported by comprehensive information technology guarantees high quality and complex data. Our younger colleagues, young scientists, post-docs or PhD students are well-trained and qualified in utilizing these new methods.
Keywords: lékaři; akademický sbor lékařské fakulty; History, 20th Century; Male; lidé; Slovenská republika; Humans; Biomedical Research; dějiny 21. století; biomedicínský výzkum; Faculty, Medical; mužské pohlaví; internacionalita; mechanika dýchání; Physicians; dějiny 20. století; History, 21st Century; Internationality; poruchy dýchání; Respiration Disorders; Respiratory Mechanics; Slovakia